A quartz crucible mold for growing semiconductor and photovoltaic monocrystalline silicon and a preparation method thereof
Patent Information
- Application Number
- CN202611267408.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]本发明的目的在于:提供了一种半导体及光伏单晶硅生长用石英坩埚模具及制备方法,解决了现有碳碳复合材料石英坩埚模具存在的抗硅蒸气渗透性差、热应力集中导致层间剥离、模具膨胀开裂的问题
[0024]1.一种半导体及光伏单晶硅生长用石英坩埚模具通过三层结构实现了热膨胀系数的梯度过渡,有效缓解了层间热应力集中;同时,内层聚碳硅烷/羧基化碳纳米管/硼酚醛树脂复合物与中间层端氨基超支化聚硅氧烷改性环氧树脂/呋喃树脂复合体系在界面处形成过渡区,进一步提高了层间结合强度;
Smart Images

Figure CN122916409A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of quartz crucible mold processing technology, and relates to a quartz crucible mold for semiconductor and photovoltaic single crystal silicon growth and its preparation method. Background Technology
[0002] Existing quartz crucible molds mostly use isostatically pressed graphite materials, whose high-temperature flexural strength at 1600℃ is typically below 50MPa, and the number of thermal shock cycles is less than 50. In recent years, some improved solutions have used homogeneous carbon-carbon composite materials, using chemical vapor deposition (CVI) to improve density. However, their flexural strength at 1600℃ is only 220-250MPa, and they have the following problems: poor resistance to silicon vapor penetration: the porosity of the homogeneous material surface is >10%, allowing silicon vapor to easily penetrate and cause the mold to expand and crack, with a penetration depth ≥0.5mm; thermal stress concentration: the material has a large gradient difference in the coefficient of thermal expansion (CTE), and the interfacial stress during rapid cooling and heating is >200MPa, causing interlayer delamination. Summary of the Invention
[0003] The purpose of this invention is to provide a quartz crucible mold and its preparation method for semiconductor and photovoltaic single crystal silicon growth, which solves the problems of poor silicon vapor permeability resistance, interlayer delamination caused by thermal stress concentration, and mold expansion and cracking in existing carbon-carbon composite quartz crucible molds.
[0004] The technical solution adopted in this invention is as follows:
[0005] A quartz crucible mold for growing semiconductor and photovoltaic monocrystalline silicon has a three-layer structure from the inside out: an inner layer, a middle layer, and an outer layer.
[0006] Inner layer structure: thickness 3-5mm, density of inner layer structure ≥1.8g / cm³ 3 The carbon fiber orthogonal layup modified by resin composite is obtained by first CVI densification, carbonization, and then second CVI densification. The carbon fiber orthogonal layup modified by resin composite is a preform obtained by impregnating carbon fiber orthogonal layup cloth with polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite and then hot pressing and curing.
[0007] Intermediate layer structure: 14-15mm thick, obtained by impregnation of three-dimensional carbon fiber braid with modified resin matrix and then carbonization; wherein, the modified resin matrix is a composite resin of amino-terminated hyperbranched polysiloxane modified epoxy resin and furan resin.
[0008] Outer layer structure: 7-8 mm thick, obtained by first CVI densification of a furan resin / chopped carbon fiber / graphite powder composite matrix, followed by carbonization and then a second CVI densification; the density of the outer layer structure is ≥1.4 g / cm³. 3 .
[0009] Furthermore, the polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite was prepared by the following method: a carboxylated carbon nanotube dispersion was added to boron phenolic resin, followed by the addition of p-toluenesulfonic acid, the amount of p-toluenesulfonic acid being 0.5%-1% of the mass of boron phenolic resin. The mixture was stirred and reacted at 100-120°C for 3-5 hours, then cooled to 80°C. An anhydrous ethanol solution of polycarbosilane was added, followed by the addition of a chloroplatinic acid catalyst, the amount of which was 0.01%-0.03% of the mass of polycarbosilane. After the initial reaction, the mixture was stirred and reacted continuously. The reaction method was to keep the mixture at 80°C and stir for 1-2 hours, then raise the temperature to 100°C and continue stirring and reacting at 100°C for 1 hour, and finally raise the temperature to 120°C and continue stirring and reacting at 120°C for 1 hour. After the reaction was completed, vacuum degassing was performed to obtain a polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite. The amount of polycarbosilane added was 10%-15% of the mass of boron phenolic resin, and the amount of carboxylated carbon nanotube added was 1%-2% of the mass of boron phenolic resin.
[0010] Further, the resin composite modified carbon fiber orthogonal layup was prepared by the following method: The carbon fiber orthogonal layup fabric was immersed in an anhydrous ethanol dilution of a polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite, wherein the mass ratio of the polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite to anhydrous ethanol was 18:82. The impregnation was performed with ultrasonic assistance for 20-40 min, followed by pressure holding at a vacuum of -0.095 to -0.1 MPa for 10 min to complete the impregnation. After impregnation, the fabric was removed and pre-dried at 80°C for 1-2 h, and then further dried at 12°C. The impregnated fabric is obtained by drying at 0℃ for 30 minutes. The impregnated fabric is then stacked to the target thickness and placed in a mold. Under a pressure of 5-10 MPa, it is first hot-pressed at 150℃ for 30 minutes, then hot-pressed at 170-180℃ for 1 hour, and finally hot-pressed at 185-190℃ for 1-2 hours. The temperature is increased by 1-3℃ / min between the above sections to obtain a preform. The preform is a resin composite modified carbon fiber orthogonal layup. During impregnation, each square meter of carbon fiber orthogonal layup corresponds to 250g of polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite.
[0011] Furthermore, the modified resin matrix in the intermediate layer structure is prepared by the following method: amino-terminated hyperbranched polysiloxane is added to bisphenol A epoxy resin E-51 at 9%~10% of the mass of bisphenol A epoxy resin E-51, and stirred at 60-80℃ for 1-2 hours to obtain amino-terminated hyperbranched polysiloxane modified epoxy resin; the amino-terminated hyperbranched polysiloxane modified epoxy resin is mixed with furan resin at a mass ratio of 2:3 to obtain a mixture; acetone is added to the mixture to make the viscosity of the mixture 600~900 cP; then maleic anhydride at 1~2% of the mass of the mixture is added, and stirred evenly to obtain the modified resin matrix.
[0012] Furthermore, the inner layer contains an M40J carbon fiber orthogonal layup fabric with a 0° / 90° orthogonal layup.
[0013] Furthermore, the three-dimensional carbon fiber braid in the intermediate layer is a three-dimensional four-directional braid of T800 carbon fiber with a braiding angle of 55°±5°.
[0014] Furthermore, in the furan resin / chopped carbon fiber / graphite powder composite matrix, the chopped carbon fiber is T300 chopped fiber with a length of 3-5 mm, and the particle size of the graphite powder is 20-50 μm; the mass ratio of T300 chopped fiber to graphite powder is 3:2.
[0015] A method for preparing a quartz crucible mold for growing semiconductor and photovoltaic single-crystal silicon includes the following steps:
[0016] S1. Preparation of the inner layer preform: The orthogonally laid carbon fiber fabric is immersed in an anhydrous ethanol dilution of a polysilane / carboxylated carbon nanotube / boron phenolic resin composite, wherein the mass ratio of the polysilane / carboxylated carbon nanotube / boron phenolic resin composite to anhydrous ethanol is 18:82. The impregnation is performed with ultrasonic assistance for 20-40 minutes, followed by pressure holding at a vacuum of -0.095 to -0.1 MPa for 10 minutes to complete the impregnation. After impregnation, the fabric is removed and pre-dried at 80℃ for 1-2 hours, then dried at 120℃ for 30 minutes. min, to obtain the impregnated cloth; stack the impregnated cloth to the target thickness, place it in the mold, and hot press it at 150℃ for 30 min under a pressure of 5-10 MPa, then hot press it at 170-180℃ for 1 h, and finally hot press it at 185-190℃ for 1-2 h. The temperature is increased by 1-3℃ / min between the above sections to obtain the inner layer preform, which serves as the core material of the quartz crucible mold; during impregnation, each square meter of carbon fiber orthogonal layup corresponds to 250g of polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite.
[0017] S2. Preparation of the intermediate layer preform: The three-dimensional carbon fiber braid is placed in a vacuum pressure impregnation tank and evacuated to below -0.09 MPa. A modified resin matrix is injected, with a mass ratio of the three-dimensional carbon fiber braid to the modified resin matrix of 1:1.2~1.8. The pressure is increased to 2.0-3.5 MPa and held for 2-4 hours. After removal, it is dried to obtain the intermediate layer preform. The intermediate layer preform is then wrapped around the core material of a quartz crucible mold according to the target thickness and cured at 160℃ for 4 hours to obtain the composite preform.
[0018] S3. Preparation of the outer layer preform: Short-cut fibers and graphite powder are dry-mixed evenly according to the mass ratio to obtain a dry mixture. Furan resin accounting for 35% of the mass of the mixture is added to the dry mixture and stirred evenly to obtain a mixture. The mixture is placed in a mold and cold-pressed at 3MPa to obtain the outer layer preform. The outer layer preform is a furan resin / short-cut carbon fiber / graphite powder composite matrix. An interlayer reactant is uniformly coated on both the outer surface of the composite preform and the inner surface of the outer layer preform. Then, the outer layer preform is tightly fitted onto the outside of the composite preform and hot-pressed at 180℃ and 4.5MPa for 2-3 hours to obtain a three-layer composite preform.
[0019] S4. First Stage CVI: Under conditions of 1100℃~1150℃ and pressure of 1~3kPa, using a mixture of methane and argon with a volume ratio of 1:3 as the gas source, chemical vapor infiltration deposition is performed on the three-layer composite preform for 200~400 hours to achieve a density of 1.8g / cm³ for the inner layer structure of the three-layer composite preform. 3 above;
[0020] S5. Carbonization: Impregnate the three-layer composite preform after the first stage CVI treatment in furan resin. After impregnation, carbonize at 1200℃ under nitrogen protection. Repeat the impregnation-carbonization operation 4-6 times to obtain the carbonized preform.
[0021] S6. Second Stage CVI: Under conditions of 900~1000℃ and 10~20kPa pressure, using a mixture of propylene and nitrogen (volume ratio 1:4) as the gas source, the carbonized preform is subjected to chemical vapor infiltration deposition for 80~120 hours to obtain a quartz crucible mold. The density of the outer layer structure of the quartz crucible mold is ≥1.4g / cm³. 3 .
[0022] Furthermore, in step S3, the interlayer reactant is an ethanol solution of boron phenolic resin containing KH-550 silane coupling agent, with a solid content of 40%, and the amount of KH-550 added is 4.5% of the mass of boron phenolic resin.
[0023] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0024] 1. A quartz crucible mold for growing semiconductor and photovoltaic monocrystalline silicon achieves a gradient transition of thermal expansion coefficient through a three-layer structure, effectively alleviating the concentration of interlayer thermal stress; at the same time, the inner layer polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite and the middle layer end-amino hyperbranched polysiloxane modified epoxy resin / furan resin composite system form a transition zone at the interface, further improving the interlayer bonding strength;
[0025] 2. In the three-layer structure of this invention, both the outer surface of the outer layer and the inner surface of the inner layer are densified, which can effectively prevent silicon vapor from permeating. Attached Figure Description
[0026] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort, wherein:
[0027] Figure 1 This is a comparative schematic diagram of the high-temperature bending strength of the quartz crucible mold in Embodiment 1 and Comparative Example 1 of the present invention;
[0028] Figure 2 This is a schematic diagram of the structure of the quartz crucible mold of the present invention. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention; that is, the described embodiments are merely some embodiments of the invention, and not all embodiments. The components of the embodiments of the invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.
[0030] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.
[0031] It should be noted that relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0032] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0033] The present invention provides a quartz crucible mold for growing semiconductor and photovoltaic single crystal silicon, which has a three-layer structure from the inside out: an inner layer, a middle layer, and an outer layer.
[0034] Inner layer structure: thickness 3-5mm, density of inner layer structure ≥1.8g / cm³ 3 The carbon fiber orthogonal layup modified by resin composite is obtained by first CVI densification, carbonization, and then second CVI densification. The carbon fiber orthogonal layup modified by resin composite is a preform obtained by impregnating carbon fiber orthogonal layup cloth with polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite and then hot pressing and curing.
[0035] Intermediate layer structure: 14-15mm thick, obtained by impregnation of three-dimensional carbon fiber braid with modified resin matrix and then carbonization; wherein, the modified resin matrix is a composite resin of amino-terminated hyperbranched polysiloxane modified epoxy resin and furan resin.
[0036] Outer layer structure: 7-8 mm thick, obtained by first CVI densification of a furan resin / chopped carbon fiber / graphite powder composite matrix, followed by carbonization and then a second CVI densification; the density of the outer layer structure is ≥1.4 g / cm³. 3 .
[0037] In the following examples, the polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite was prepared by the following method:
[0038] A dispersion of carboxylated carbon nanotubes (containing 1.5 g of carboxylated carbon nanotubes) was added to 100 g of boron phenolic resin, followed by 0.8 g of p-toluenesulfonic acid. The mixture was stirred at 110 °C for 4 hours. The temperature was then lowered to 80 °C, and an anhydrous ethanol solution containing 12 g of polycarbosilane was added, along with 0.003 g of chloroplatinic acid catalyst. After the addition was complete, the mixture was stirred at 80 °C for 1.5 hours, then heated to 100 °C and stirred for another hour. Finally, the temperature was raised to 120 °C and stirred for another hour. After the reaction, the mixture was degassed under vacuum to obtain a polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite. In practical applications, the ratio of each component can be scaled up according to the usage.
[0039] In the following examples, the resin composite modified carbon fiber orthogonal layup was prepared by the following method: 1m of M40J carbon fiber 0° / 90° orthogonal layup fabric was prepared. 2The carbon fiber was immersed in an anhydrous ethanol dilution containing 250g of a polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite, with a mass ratio of the polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite to anhydrous ethanol of 18:82. The immersion was ultrasonically assisted for 30 minutes, followed by pressure holding at -0.098MPa for 10 minutes to complete the immersion. After immersion, the immersion fabric was removed and pre-dried at 80℃ for 1.5 hours, then dried at 120℃ for 30 minutes to obtain the impregnated fabric. The impregnated fabric was then stacked to the target thickness, placed in a mold, and hot-pressed at 150℃ for 30 minutes under a pressure of 8MPa, followed by hot-pressing at 175℃ for 1 hour, and finally hot-pressing at 185℃ for 1.5 hours, with a temperature increase of 2℃ / min between each section, to obtain a preform. The preform is a resin composite modified carbon fiber orthogonal layup. In actual use, the proportions of each component can be scaled up proportionally according to the usage.
[0040] In the following embodiments, the modified resin matrix in the intermediate layer structure was prepared by the following method: Amino-terminated hyperbranched polysiloxane was added to bisphenol A epoxy resin E-51 at 9.5% of its mass, and the mixture was stirred at 70°C for 1.5 hours to obtain an amino-terminated hyperbranched polysiloxane-modified epoxy resin. The amino-terminated hyperbranched polysiloxane-modified epoxy resin was then mixed with furan resin at a mass ratio of 2:3 to obtain a mixture. Acetone was added to the mixture to achieve a viscosity of 800 cP. Subsequently, maleic anhydride at 1.5% of the mixture mass was added, and the mixture was stirred until homogeneous to obtain the modified resin matrix. After homogeneous stirring, the matrix was used for impregnating T800 carbon fiber three-dimensional four-way braided structures.
[0041] In the following embodiments, the three-dimensional carbon fiber braid in the intermediate layer is a three-dimensional four-way braid of T800 carbon fiber with a braiding angle of 55°±5°.
[0042] In the following embodiments, the chopped carbon fibers in the furan resin / chopped carbon fiber / graphite powder composite matrix are T300 chopped fibers with a length of 3-5 mm, and the particle size of the graphite powder is 20-50 μm; the mass ratio of T300 chopped fibers to graphite powder is 3:2.
[0043] Example 1
[0044] This embodiment provides a quartz crucible mold for growing semiconductor and photovoltaic single-crystal silicon, which is prepared by the following method:
[0045] S1. Preparation of the inner layer preform: Lay 1m of M40J carbon fiber 0° / 90° orthogonal layer fabric. 2The material is immersed in an anhydrous ethanol dilution containing 250g of a polysilane / carboxylated carbon nanotube / boron phenolic resin composite, with a mass ratio of the polysilane / carboxylated carbon nanotube / boron phenolic resin composite to anhydrous ethanol of 18:82. The immersion is ultrasonically assisted for 30 minutes, followed by pressure holding at a vacuum of -0.098MPa for 10 minutes to complete the immersion. After immersion, the material is removed and pre-dried at 80℃ for 1.5 hours, then dried at 120℃ for 30 minutes to obtain the impregnated fabric. The impregnated fabric is then stacked to the target thickness, placed in a mold, and hot-pressed at 150℃ for 30 minutes under a pressure of 8MPa, followed by hot-pressing at 175℃ for 1 hour, and finally hot-pressing at 185℃ for 1.5 hours, with a temperature increase of 2℃ / min between each section, to obtain the inner layer preform, which serves as the core material for the quartz crucible mold.
[0046] S2. Preparation of the intermediate layer preform: Place the T800 carbon fiber three-dimensional four-way braid (braiding angle of 55°±5°) in a vacuum pressure impregnation tank, evacuate to below -0.09MPa, inject the modified resin matrix, the mass ratio of T800 carbon fiber three-dimensional four-way braid to modified resin matrix is 1:1.5; pressurize to 3MPa, hold pressure for 3 hours, remove and air dry to obtain the intermediate layer preform; wrap the intermediate layer preform around the core material of the quartz crucible mold according to the target thickness, and cure at 160℃ for 4 hours to obtain the composite preform;
[0047] S3. Preparation of the outer preform: T300 chopped fibers and graphite powder are dry-mixed evenly at a mass ratio of 3:2 to obtain a dry mixture. Furan resin, accounting for 35% of the mass of the mixture, is added to the dry mixture and stirred evenly to obtain a mixture. The mixture is placed in a mold and cold-pressed at 3MPa to obtain an outer preform that matches the shape and size of the composite preform. An interlayer reactant is evenly coated on both the outer surface of the composite preform and the inner surface of the outer preform. Then, the outer preform is tightly fitted onto the outside of the composite preform and hot-pressed at 180℃ and 4.5MPa for 2.5 hours to obtain a three-layer composite preform. The interlayer reactant is a boron phenolic resin ethanol solution containing KH-550 silane coupling agent, with a solid content of 40%, and the amount of KH-550 added is 4.5% of the mass of the boron phenolic resin.
[0048] S4. First Stage CVI: Under conditions of 1120℃ and 2kPa pressure, using a mixture of methane and argon at a volume ratio of 1:3 as the gas source, chemical vapor infiltration deposition is performed on the three-layer composite preform for 300 hours to achieve a density of the inner layer structure of the three-layer composite preform greater than 1.8 g / cm³. 3 ;
[0049] S5. Carbonization: The three-layer composite preform after the first stage CVI treatment is impregnated in furan resin. After impregnation, it is carbonized at 1200℃ for 2 hours under nitrogen protection. The above impregnation-carbonization operation is repeated 5 times to obtain the carbonized preform. The mass ratio of the three-layer composite preform to furan resin in a single impregnation is 1:2.
[0050] S6. Second Stage CVI: Under conditions of 950℃ and 15kPa pressure, using a propylene-nitrogen mixture (volume ratio 1:4) as the gas source, the carbonized preform is subjected to chemical vapor infiltration deposition for 100 hours, resulting in a density greater than 1.4 g / cm³ for the outer layer structure of the quartz crucible mold. 3 The quartz crucible mold was obtained, and its structural diagram is shown below. Figure 2 As shown.
[0051] Example 2
[0052] This embodiment differs from Embodiment 1 in that the mass ratio of the T800 carbon fiber three-dimensional four-way braid to the modified resin matrix in step S2 is 1:1.2. All other aspects remain the same.
[0053] Example 3
[0054] This embodiment differs from Embodiment 1 in that the mass ratio of the T800 carbon fiber three-dimensional four-way braid to the modified resin matrix in step S2 is 1:1.8. All other aspects remain the same.
[0055] Comparative Example 1
[0056] This comparative example provides a crucible mold, which is prepared by the following method: M40J carbon fiber is arranged in a 0° / 90° orthogonal layer in an impregnation tank, and immersed in an anhydrous ethanol dilution of pure boron phenolic resin (250g of pure boron phenolic resin per square meter of carbon fiber cloth). The impregnation is ultrasonically assisted for 30 minutes, and then held under vacuum of -0.098MPa for 10 minutes to complete the impregnation. After removal, it is pre-dried in an 80℃ forced-air oven for 1.5 hours, and then dried at 120℃ for 30 minutes to obtain the impregnated cloth. The impregnated cloth is stacked to the target thickness (corresponding to the total thickness of the three layers in Example 1), placed in the mold, and hot-pressed at 150℃ for 30 minutes under a pressure of 8MPa → at 2℃ / m The homogeneous preform was cured by hot pressing at 175℃ for 1 hour, followed by hot pressing at 185℃ for 1.5 hours at a rate of 2℃ / min. The preform was then subjected to chemical vapor deposition (CVD) at 1120℃ and 2 kPa using a 1:3 volume ratio of methane to argon as the gas source for 400 hours. Subsequently, it was impregnated with furan resin (preform to furan resin mass ratio 1:2) and carbonized at 1200℃ for 2 hours under nitrogen protection. This impregnation-carbonization process was repeated 5 times. Finally, the crucible mold was obtained by CVD at 950℃ and 15 kPa using a 1:4 volume ratio of propylene to nitrogen as the gas source for 100 hours.
[0057] Comparative Example 2
[0058] This comparative example differs from Example 1 in that: in the preparation of the inner layer preform, unmodified pure boron phenolic resin is used instead of polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite to impregnate the carbon fiber orthogonal layup, and no polycarbosilane or carboxylated carbon nanotubes are added; the remaining steps and parameters are the same as in Example 1.
[0059] Comparative Example 3
[0060] This comparative example differs from Example 1 in that it does not include an intermediate layer. In step S3, the interlayer reactant is directly coated on the outer surface of the inner preform and the inner surface of the outer preform. Then, the outer preform is tightly fitted onto the outside of the inner preform and hot-pressed at 180°C and 4.5 MPa for 2.5 hours to obtain a two-layer composite preform. The remaining steps are the same as in Example 1.
[0061] Comparative Example 4
[0062] This comparative example differs from Example 1 in that: in the intermediate layer preform of this comparative example, unmodified bisphenol A epoxy resin E-51 is used instead of amino-terminated hyperbranched polysiloxane modified epoxy resin; the remaining steps and parameters are the same as in Example 1.
[0063] Experimental Example 1
[0064] The flexural strength at 1600℃, the number of thermal shock cycles, and the silicon vapor penetration depth of the crucible molds prepared in Examples 1-3 and Comparative Examples 1-4 were tested. Five parallel samples were used in each group, and the average value was taken. The results are shown in Table 1.
[0065] 1600℃ Bending Strength Test: Based on the actual total thickness h of the mold, the span was set at a span-to-thickness ratio L / h = 16:1 (i.e., span = 16h). Full-thickness specimens containing an inner layer, middle layer, and outer layer were cut from the crucible mold. The specimen length was not less than the span + 20mm (actually 16h + 20mm), and the width was 20mm. Under an argon protective atmosphere, the bending strength of each group of specimens was tested at 1600℃ using the three-point bending method (loading rate 1mm / min). A comparison of the bending strength changes at various temperatures between Example 1 and Comparative Example 1 is provided. Figure 1 As shown.
[0066] Thermal shock cycle test: The crucible molds prepared in Examples 1-3 and Comparative Examples 1-4 were placed in a high-temperature furnace and heated to 1600°C at a heating rate of 10°C / min under an argon protective atmosphere. The temperature was held for 30 minutes to ensure uniform temperature distribution. The molds were then quickly removed and quenched in a 25°C flowing deionized water bath. The time between removing the mold from the high-temperature furnace and immersing it in the water bath should not exceed 10 seconds. After removing the mold and drying its surface, the inner and outer walls were inspected for cracks. Ultrasonic testing was also used to detect interlayer defects inside the mold. If no cracks or delamination were found on the surface or inside the mold, it was recorded as one thermal shock cycle. The mold was then placed back into the high-temperature furnace, and the heating-holding-quenching-testing operation was repeated. The number of cycles at which a through-crack or delamination first appeared was recorded as the thermal shock cycle count for that crucible mold.
[0067] Silicon vapor penetration depth detection: The crucible molds prepared in Examples 1-3 and Comparative Examples 1-4 were placed with the inner layer facing upwards and exposed to a silicon vapor (SiO partial pressure of about 0.1 atm) environment at 1600℃ for 100h. After cooling, they were cut along the thickness direction and the maximum penetration depth from the inner layer surface to the interior was measured using a scanning electron microscope.
[0068] Table 1 Performance test results of crucible molds
[0069] Flexural strength at 1600℃ thermal shock cycles Silicon vapor penetration depth Example 1 328MPa 500 times 0.04mm Example 2 315MPa 452 times 0.05mm Example 3 322MPa 504 times 0.04mm Comparative Example 1 235MPa 45 times 0.60mm Comparative Example 2 268MPa 151 times 0.28mm Comparative Example 3 252MPa 83 times 0.35mm Comparative Example 4 285MPa 210 times 0.15mm
[0070] As shown in Table 1, the quartz crucible molds prepared in Examples 1-3 of this invention are significantly superior to the comparative examples in terms of flexural strength at 1600℃ (315~328MPa), thermal shock cycle count (452~504 cycles), and silicon vapor penetration depth (0.04~0.05mm). Compared with existing crucible molds made of homogeneous materials such as Comparative Example 1, the above properties are significantly improved.
[0071] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A quartz crucible mold for growing semiconductor and photovoltaic single-crystal silicon, characterized in that: It has a three-layer structure from the inside out: inner layer, middle layer, and outer layer. Inner layer structure: thickness 3-5mm, density of inner layer structure ≥1.8g / cm³ 3 The carbon fiber orthogonal layup modified by resin composite is obtained by first CVI densification, carbonization, and then second CVI densification. The carbon fiber orthogonal layup modified by resin composite is a preform obtained by impregnating carbon fiber orthogonal layup cloth with polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite and then hot pressing and curing. Intermediate layer structure: 14-15mm thick, obtained by impregnation of three-dimensional carbon fiber braid with modified resin matrix and then carbonization; wherein, the modified resin matrix is a composite resin of amino-terminated hyperbranched polysiloxane modified epoxy resin and furan resin. Outer layer structure: 7-8 mm thick, obtained by first CVI densification of a furan resin / chopped carbon fiber / graphite powder composite matrix, followed by carbonization and then a second CVI densification; the density of the outer layer structure is ≥1.4 g / cm³. 3 .
2. The quartz crucible mold for semiconductor and photovoltaic single-crystal silicon growth according to claim 1, characterized in that: A polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite was prepared by the following method: a carboxylated carbon nanotube dispersion was added to boron phenolic resin, followed by the addition of p-toluenesulfonic acid, the amount of p-toluenesulfonic acid being 0.5%-1% of the mass of boron phenolic resin. The mixture was stirred at 100-120℃ for 3-5 hours, then cooled to 80℃. An anhydrous ethanol solution of polycarbosilane was added, followed by the addition of chloroplatinic acid catalyst, the amount of chloroplatinic acid catalyst being 0.01%-0.03% of the mass of polycarbosilane. The reaction mixture was then subjected to further processing. After the reaction is completed, the mixture is stirred and reacted at 80°C for 1-2 hours. Then the temperature is raised to 100°C and stirred and reacted at 100°C for 1 hour. Finally, the temperature is raised to 120°C and stirred and reacted at 120°C for 1 hour. After the reaction is completed, the mixture is degassed under vacuum to obtain a polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite. The amount of polycarbosilane added is 10%-15% of the mass of boron phenolic resin, and the amount of carboxylated carbon nanotube added is 1%-2% of the mass of boron phenolic resin.
3. The quartz crucible mold for semiconductor and photovoltaic single-crystal silicon growth according to claim 1, characterized in that: The resin composite modified carbon fiber orthogonal layup was prepared by the following method: the carbon fiber orthogonal layup fabric was immersed in an anhydrous ethanol dilution of polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite, ultrasonically assisted impregnation was performed, and then pressure was maintained at a vacuum of -0.095 to -0.1 MPa to complete the impregnation; after impregnation, it was removed and pre-dried at 80℃ for 1-2 hours, and then dried at 120℃ for 30 minutes to obtain the impregnated fabric; the impregnated fabric was stacked to the target thickness, placed in a mold, and hot-pressed at 150℃ for 30 minutes under a pressure of 5-10 MPa, then hot-pressed at 170-180℃ for 1 hour, and finally hot-pressed at 185-190℃ for 1-2 hours to obtain the preform, which is the resin composite modified carbon fiber orthogonal layup.
4. The quartz crucible mold for semiconductor and photovoltaic single-crystal silicon growth according to claim 1, characterized in that: The modified resin matrix in the intermediate layer structure is prepared by the following method: 9% to 10% of the mass of bisphenol A epoxy resin E-51 with terminal amino hyperbranched polysiloxane is added to the bisphenol A epoxy resin E-51, and the mixture is stirred at 60-80°C for 1-2 hours to obtain terminal amino hyperbranched polysiloxane modified epoxy resin; the terminal amino hyperbranched polysiloxane modified epoxy resin is mixed with furan resin at a mass ratio of 2:3 to obtain a mixture; acetone is added to the mixture to make the viscosity of the mixture 600-900 cP; then maleic anhydride is added at 1-2% of the mass of the mixture, and the mixture is stirred evenly to obtain the modified resin matrix.
5. The quartz crucible mold for semiconductor and photovoltaic single-crystal silicon growth according to claim 1, characterized in that: The inner layer contains M40J carbon fiber orthogonal layup fabric with a 0° / 90° orthogonal layup.
6. The quartz crucible mold for semiconductor and photovoltaic single-crystal silicon growth according to claim 1, characterized in that: The three-dimensional carbon fiber braid in the intermediate layer is a T800 carbon fiber three-dimensional four-way braid with a braiding angle of 55°±5°.
7. The quartz crucible mold for semiconductor and photovoltaic single-crystal silicon growth according to claim 1, characterized in that: The furan resin / chopped carbon fiber / graphite powder composite matrix contains T300 chopped carbon fibers with a length of 3-5 mm and graphite powder with a particle size of 20-50 μm; the mass ratio of T300 chopped carbon fibers to graphite powder is 3:
2.
8. A method for preparing a quartz crucible mold for semiconductor and photovoltaic single-crystal silicon growth according to any one of claims 1-7, characterized in that: Includes the following steps: S1. Preparation of the inner layer preform: The carbon fiber orthogonal lay-up fabric is immersed in an anhydrous ethanol dilution of polycarbosilane / carboxylated carbon nanotube / boron phenolic resin composite, and ultrasonically assisted impregnation is performed for 20-40 min. Then, it is held under vacuum of -0.095 to -0.1 MPa for 10 min to complete the impregnation. After the impregnation is completed, it is removed and pre-dried at 80℃ for 1-2 h, and then dried at 120℃ for 30 min to obtain the impregnated fabric. The impregnated cloth is stacked to the target thickness and placed in the mold. Under a pressure of 5-10 MPa, it is first hot-pressed at 150℃ for 30 minutes, then hot-pressed at 170-180℃ for 1 hour, and finally hot-pressed at 185-190℃ for 1-2 hours to obtain the inner layer preform, which serves as the core material for the quartz crucible mold. S2. Preparation of the intermediate layer preform: The three-dimensional carbon fiber braid is placed in a vacuum pressure impregnation tank and evacuated to below -0.09 MPa. A modified resin matrix is injected, with a mass ratio of the three-dimensional carbon fiber braid to the modified resin matrix of 1:1.2~1.
8. The pressure is increased to 2.0-3.5 MPa and held for 2-4 hours. After removal, it is dried to obtain the intermediate layer preform. The intermediate layer preform is then wrapped around the core material of a quartz crucible mold according to the target thickness. After curing for 4 hours, the composite preform is obtained. S3. Preparation of the outer preform: Short-cut fibers and graphite powder are dry-mixed evenly according to the mass ratio to obtain a dry mixture. Furan resin is added to the dry mixture and stirred evenly to obtain a mixture. The mixture is placed in a mold and cold-pressed to obtain the outer preform. The outer preform is a furan resin / short-cut carbon fiber / graphite powder composite matrix. An interlayer reactant is uniformly coated on both the outer surface of the composite preform and the inner surface of the outer preform. Then, the outer preform is tightly fitted onto the outside of the composite preform and hot-pressed at 180℃ and 4.5MPa for 2-3 hours to obtain a three-layer composite preform. S4. First Stage CVI: Under conditions of 1100℃~1150℃ and pressure of 1~3kPa, using a mixture of methane and argon with a volume ratio of 1:3 as the gas source, chemical vapor infiltration deposition is performed on the three-layer composite preform for 200~400 hours to achieve a density of 1.8g / cm³ for the inner layer structure of the three-layer composite preform. 3 above; S5. Carbonization: Impregnate the three-layer composite preform after the first stage CVI treatment in furan resin. After impregnation, carbonize at 1200℃ under nitrogen protection. Repeat the impregnation-carbonization operation 4-6 times to obtain the carbonized preform. S6. Second Stage CVI: Under conditions of 900~1000℃ and 10~20kPa pressure, using a mixture of propylene and nitrogen (volume ratio 1:4) as the gas source, the carbonized preform is subjected to chemical vapor infiltration deposition for 80~120 hours to obtain a quartz crucible mold. The density of the outer layer structure of the quartz crucible mold is ≥1.4g / cm³. 3 .
9. The method for preparing a quartz crucible mold for semiconductor and photovoltaic single-crystal silicon growth according to claim 8, characterized in that: In step S3, the interlayer reaction agent is an ethanol solution of boron phenolic resin containing KH-550 silane coupling agent, with a solid content of 40%, and the amount of KH-550 added is 4.5% of the mass of boron phenolic resin.